Radioisotope and Metal Concentrations in Borehole Water Samples of Umuahia and Umudike, Nigeria - J.C. Nnaji; O.U. Igwe; K.M. Onyedim; P. Okafor (Journal of Applied Sciences and Environmental Management)
The study examined metal and radioisotope concentrations in boreholes water samples collected from the neighbouring towns of in Umuahia and Umudike, Abia State, Nigeria. Triplicate samples were collected from seventeen functional boreholes and were analyzed with standard methods for physicochemical parameters. Metal concentrations were analyzed with Graphite furnace Atomic Absorption Spectrophotometer (AAS) while radioisotopes were determined with gamma ray spectrometry. Results showed that mean values for conductivity, total solids, total dissolved solids, hardness and nitrates were lower than recommended values by the World Health Organization (WHO) and Standards Organization of Nigeria (SON). However, mean values for pH (range: 3.05±0.11 – 4.51±0.08) were in the acidic region and outside the recommended values. Mean metal concentrations had ranges of: calcium 1.255±0.037 – 1.967±0.078 mg/L; magnesium 0.286±0.057 – 0.608±0.094 mg/L; sodium 0.030±0.005 – 0.102±0.029 mg/L; iron 0.012±0.001 – 0.019±0.004 mg/L; cadmium 0.001±0.000 – 0.011±0.003 mg/L and lead (Pb) 0.077±0.005 – 0.198±0.040 mg/L. The mean concentrations of calcium, sodium, magnesium and iron were all below the NSDWQ limits. However, while mean cadmium concentrations exceeded SON limits in 13 locations, mean lead concentrations were above the limits set by WHO and SON in the samples from all the boreholes. The mean activity concentrations K-40, U-238 and Th-232 had ranges of below detection limit (BDL) – 21.94±2.50 Bq/L; BDL – 7.85 ±1.80 Bq/L and BDL – 5.76 ±0.53 respectively. The SON maximum level for radionuclides in water is 0.1 Bq/L while the WHO limits for U-238 and Th-232 are 10 and 1 Bq/L respectively. The activity concentrations of U-238 were below the WHO limits but the limits were exceeded for Th-232 in water samples from eight locations. The NSDWQ limits were exceeded in samples from most of the locations for K-40.